Climate change impacts on the nexus between water, energy and food resources : the cases of Narok County in Kenya and Vhembe District Municipality, in South Africa - Botai, Joel (University of Pretoria, 2025)
Thesis (PhD (Meteorology))--University of Pretoria, 2025.